Perceptions of environmental services staff regarding disinfectants for cleaning in healthcare facilities - Young, Brianna; Schmitz, Michelle; Thomas, Kevin; Weiler, Beth; Safdar, Nasia (International Journal of Infection Control, 2016)
This report examines environmental services staff (ESS) experiences when using Clorox Bleach Wipes compared to OxyCide™ Daily Disinfectant Cleaner (a non-bleach, peroxide-based sporocide) for disinfection at an academic medical center. Other studies focus on examining the efficacy of health-care disinfection products with little to no assessment of impact on the user. We found that ESS perceives better tolerability for non-bleach, peroxide-based sporocides compared with bleach-based products. Future studies should consider end user perceptions and experience when examining disinfection products.